2021
DOI: 10.21608/ejvs.2021.70487.1227
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium and Giardia Infection in Pet Animals: A review Study in Iraq

Abstract: C ryptosporidium parvum and Giardia lamblia are the most common zoonotic intestinal protozoan parasites causing diarrheal diseases Cryptosporidiosis and Giardiasis are significant health concerns in both humans and animals; for this reason, these parasites acquired public and veterinary importance. Dogs and cats are susceptible to infection and play an important role in transmitting these protozoans to human. Recently in Iraq, there is an interest in keeping pet animals and an increase of stray cats and dogs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
1
6
1
Order By: Relevance
“…This study demonstrates that the highest infection rates in pets were observed in the age group under 6 months. These findings agree with the previous studies conducted in Iraqi cities by Naser and Wadood [19], Alhayali et al [22], Jasim and Faraj [23], and Latif et al [28]. Giardia duodenalis infections in dogs and cats have been investigated worldwide, with the infection prevalent in younger animals [26,[29][30][31].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study demonstrates that the highest infection rates in pets were observed in the age group under 6 months. These findings agree with the previous studies conducted in Iraqi cities by Naser and Wadood [19], Alhayali et al [22], Jasim and Faraj [23], and Latif et al [28]. Giardia duodenalis infections in dogs and cats have been investigated worldwide, with the infection prevalent in younger animals [26,[29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…In Iraq, G. duodenalis is highly endemic due to unsanitary conditions and favorable climates, and its prevalence varies across studies depending on geographical areas, local animal habitats, animal populations, and seasonal variations throughout the year. Notably, the infection rate of G. duodenalis is higher in stray cats and dogs than in pets [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giardia is a flagellated parasite, both of them parasitize in the intestine of the most mammals, birds and reptiles [1]. Giardiasis is considered as most prominent intestinal parasitic infection among companion pets (dogs and cats) in the developing countries.…”
Section: Introductionmentioning
confidence: 99%